Streptococcus pneumoniae meningitis complicated by an intramedullary abscess: a case report and review of the literature. (December 2016) - Vo, Dat; Cravens, George; Germann, Robert
Abstract Background Intramedullary abscess is a rare neurosurgical condition that usually arises in the setting of penetrating trauma to the spinal cord, infected congenital dural sinuses, or tuberculosis. Case presentation We describe a case of a 35-year-old African American male who presented with sepsis and a clinical picture of meningitis. The patient continued to have declining neurological status with decreasing sensation and worsening motor strength in all four extremities. He was found to have an intramedullary abscess in the cervical spinal cord that was treated with a decompressive posterior cervical laminectomy and drainage. The patient began to have a partial recovery of neurological function postoperatively. We also review the literature on intramedullary abscess that suggests the clinical presentation of our patient was a rare complication of acute meningitis. Conclusions Intramedullary abscess formation is a rare entity, and a high index of suspicion for intramedullary abscess is the key for making the diagnosis and expediting treatment for these patients.